The voices of disadvantaged scholarship recipient learners in affluent independent high schools - Geyer, Kelly (My University, 2014)
In an attempt to promote inclusion and to improve educational outcomes, many affluent independent high schools in South Africa offer scholarships to talented and deserving learners from economically disadvantaged backgrounds. It is often assumed that learners selected for “inclusion” in these schools benefit greatly from such an opportunity, yet the voices of these scholarship recipients are seldom heard. In this qualitative study, grounded in the methodology of phenomenography, a multimodal approach was adopted to listen to the voices of the participants, so as to obtain information-rich data. By listening to the experiences of the learner participants in a study that was framed by the concept of ‘voice research’, it was found that while the learners are grateful for the opportunity to attend affluent independent high schools, they are also aware of the limits of benevolence1. When learners’ perceptions regarding their access to such independent schools were explored, it was found that learners believed that they were deserving of their scholarships, based on their proven academic performance and diligence and the potential that they showed. It was also found that learners’ full participation in the academic, sporting and social life of the school was constrained by their economic disadvantage. With reference to the findings in the literature and the voices of the participants in the study, it can be asserted that while such scholarship programmes offer many advantages, they also have limitations, which need to be addressed at an individual level.
submitted in partial fulfilment of the requirements for the degree of MASTER OF EDUCATION in the Faculty of Humanities at the UNIVERSITY OF THE WITWATERSRAND MARCH 2014